2019
DOI: 10.5535/arm.2019.43.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Sinking Skin Flap Syndrome or Syndrome of the Trephined: A Report of Two Cases

Abstract: Decompressive craniectomy (DC) is commonly performed in patients with intracranial hypertension or brain edema due to traumatic brain injury. Infrequently, neurologic deteriorations accompanied by sunken scalp may occur after DC. We report two patients with traumatic subdural hemorrhage who had neurologic deteriorations accompanied by sunken scalp after DC. Neurologic function improved dramatically in both patients after cranioplasty. Monitoring for neurologic deterioration after craniectomy is advised. For pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Triple F therapy, (1) flat head end, (2) fluid administration, and (3) flap replacement (autologous bone or mesh), is the cornerstone of the management of SFS [27]. The role of early cranioplasty in SFS is not wellelaborated, but some studies have shown the advantageous effect of early cranioplasty in SFS [28,29]. Since SFS is a sequelae of PTH following shunt procedures, we propose that early cranioplasty should be considered in patients of PTH following DCs with MFHI > 43, although to verify this statement, we need more large scale prospective cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Triple F therapy, (1) flat head end, (2) fluid administration, and (3) flap replacement (autologous bone or mesh), is the cornerstone of the management of SFS [27]. The role of early cranioplasty in SFS is not wellelaborated, but some studies have shown the advantageous effect of early cranioplasty in SFS [28,29]. Since SFS is a sequelae of PTH following shunt procedures, we propose that early cranioplasty should be considered in patients of PTH following DCs with MFHI > 43, although to verify this statement, we need more large scale prospective cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Urgent operative intervention is rarely indicated; however, in patients who do not improve with conservative treatment, early cranioplasty is most effective in relieving symptoms [ 6 ]. Early cranioplasty remains a life-saving measure to perform when midline shifting is confirmed by CT and does result in better outcomes for these patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%